Tinjauan Hukum Islam Terhadap Zakat Sebagai Pengurang Penghasilan Kena Pajak(Studi Kasus di Badan Amil Zakat Nasional/BAZNAS Kabupaten Karanganyar) - Nugraha, Muhammad Hafid Adhi; , Mutimatum Ni'ami. SH..M.Hum; , Marisa Kurnianingsih., SH.MKn.MH (2016)
Zakat and tax is a subsystem that is very important in supporting the national economy . In Islam zakat is an important element and must be implemented as contained in the fourth pillar of Islam . While taxes are the obligations imposed on the taxpayer , which must be paid to the State in accordance with the provisions. Management of zakat as a deduction from taxable income in Badan Amil Zakat Nasional ( BAZNAS ) Karanganyar be one important element that is capable of being a forum for people who want to pay the zakat and taxable income that aims to help governments Karanganya district in the welfare of its citizens . Based on Government Regulation No.60 of 2010 on Zakat For Income Reduction mechanism on charity as a deduction from taxable income. Keywords : Management of zakat , zakat deduction mechanism taxable income